An error resilient and memory efficient image coder for mobile wireless channels - Md Abdul Kader (School of Computer and Communication Engineering, 2012)
The objectives set for this project is the development of an image coder with efficient compression, memory efficiency and error resilience for image transmission over unreliable heterogeneous mobile networks.